Carbon-based composites for rechargeable zinc-air batteries: A mini review - Yuzhen Liu; Junjie Lu; Shaofeng Xu; Wei Zhang; De Gao (Frontiers in Chemistry, 2022)
Rechargeable zinc-air batteries (ZABs) have gained a significant amount of attention as next-generation energy conversion and storage devices owing to their high energy density and environmental friendliness, as well as their safety and low cost. The performance of ZABs is dominated by oxygen electrocatalysis, which includes the oxygen reduction reaction (ORR) and the oxygen evolution reaction (OER). Therefore, it is crucial to develop effective bifunctional oxygen electrocatalysts that are both highly active and stable. Carbon-based materials are regarded as reliable candidates because of their superior electrical conductivity, low price, and high durability. In this Review, we briefly introduce the configuration of ZABs and the reaction mechanism of bifunctional ORR/OER catalysts. Then, the most recent developments in carbon-based bifunctional catalysts are summarized in terms of carbon-based metal composites, carbon-based metal oxide composites, and other carbon-based composites. In the final section, we go through the significant obstacles and potential future developments for carbon-based bifunctional oxygen catalysts for ZABs.